Prognostic factors of adherence to home-based exercise therapy in patients with chronic diseases: A systematic review and meta-analysis - Ricke, Ellen; Dijkstra, Arie; Bakker, Eric W. (Frontiers in Sports and Active Living, 2023)
Background: Patients with a chronic disease may have an increased risk of non-adherence to prescribed home-based exercise therapy. We performed a systematic review with the aim to identify variables associated with adherence to home-based exercise therapy in patients with chronic diseases and to grade the quality of evidence for the association between these prognostic factors and adherence. Methods: Cohort studies, cross-sectional studies and the experimental arm of randomized trials were identified using a search strategy applied to PubMed, Embase, PsychINFO and CINAHL from inception until August 1th 2022. We included studies with participants > 18 years with a chronic disease as an indication for home-based exercise therapy and providing data on prognostic factors of adherence to home-based exercise. To structure the data, we categorized the identified prognostic factors into the five WHO-domains; 1. Patient-related, 2. Social/economic, 3. Therapy-related, 4. Condition-related, and 5. Health system factors. Risk of bias was assessed using the Quality in Prognostic Studies (QUIPS) tool. Prognostic factors of adherence were identified and the quality of the evidence between the prognostic factors and adherence were graded using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework for predictor studies. We performed a meta-analysis of the obtained information. Results: A total of 57 studies were included. Within patient-related factors moderate- and high-quality evidence suggested that more self-efficacy, exercise history, motivation and perceived behavioral control predicted higher adherence. Within social-economic factors moderate-quality evidence suggested more education and physical health to be predictive of higher adherence and within condition-related factors moderate- and low-quality evidence suggested that less comorbidities, depression and fatigue predicted higher adherence. For the domains therapy-related and health-system factors there was not enough information to determine the quality evidence of the prognostic factors. Conclusion: These findings might aid the development of future home-based exercise programs as well as the identification of individuals who may require extra support to benefit from prescribed home-based exercise therapy. Registration: The protocol of this systematic review is registered in PROSPERO with registration number CRD42021277003.